Exposure levels of organophosphate pesticides in Japanese diapered children: Contributions of exposure-related behaviors and mothers' considerations of food selection and preparation. (January 2020) - Oya, Naoko; Ito, Yuki; Ebara, Takeshi; Kato, Sayaka; Hioki, Keisuke; Aoi, Arisa; Ueyama, Jun; Oguri, Tomoko; Shoji, Naoto; Sugiura-Ogasawara, Mayumi; Saitoh, Shinji; Kamijima, Michihiro
Highlights: Organophosphate (OP) pesticide exposure levels in Japanese toddlers were examined. At least one kind of dialkylphosphate (DAP) was detected in each urine sample. Some household chemical product use was associated with increased DAP levels. Foodstuffs contributed the most to OP exposure among all exposure-related factors. Abstract: Organophosphate (OP) pesticide exposure is a public health issue due to its potential link to neurodevelopmental problems in children. This study aimed to examine the exposure levels of OP pesticides in Japanese toddlers and explore the possible contributions of their exposure-related behaviors and their mothers' considerations of food selection and preparation to their exposure levels to OP pesticides. We recruited diapered children participating in the Japan Environment and Children's Study and collected used disposable diapers from 1037 children between June 2015 and August 2016. Six dialkylphosphates (DAPs) were measured in the urine extracted from the diapers. The geometric means of urinary creatinine (Cr)-unadjusted and Cr-adjusted concentrations of the sum of the six DAPs (ΣDAP) were 120 nmol/L and 243 nmol/g Cr, respectively. A receiver operating characteristic curve analysis for propensity scores of exposure-related factors revealed that discriminatory powers determining whether Cr-unadjusted and Cr-adjusted ΣDAP concentrations exceeded the 95th percentile values were lower for the exposure-related behaviors (areas under the curve, 0.72 and 0.69, respectively) and the mothers' considerations of food selection and preparation (0.55 and 0.57, respectively) than those for the foodstuffs ingested on the survey day (0.75 and 0.81, respectively). Some exposure-related behaviors, namely the use of insecticides, herbicides, and insect repellent sprays, were found to be associated with increased Cr-unadjusted ΣDAP concentrations (odds ratio, 2.0–2.6) via multivariate analysis. In contrast, only the use of a fragrance or deodorant was associated with increased Cr-adjusted ΣDAP concentrations (odds ratio, 2.3). This is the first report on the exposure levels of OP pesticides in a large number of Japanese toddlers. Some household chemical product use was related to OP common metabolite DAP levels. Japanese toddlers were widely exposed to OP pesticide.